Brain stimulation techniques and sports performance - Prete, G.; Bertollo, M.; Tommasi, L. (Advances in mental skills training, 2021)
The continuous effort to enhance personal skills can be defined as the leitmotiv for athletes and sportsmen (Kellmann et al., 2018). In the majority of cases, this leads athletes to devote several hours each day to physical training and often to spend time on mental training. A number of new technological tools are now available to further enhance the effects of physical and mental training. The use of these technologies in different sports is a new window for sport psychologists and athletes in a period in which important findings in this field are emerging and evidence of their applied effects is now available. In this chapter, we describe the basic functioning of these new techniques, mainly based on safe electrical stimulation of the nervous system. As it will be explained, current research suggests that these technologies could be a viable option to further improve the positive effects of physical and mental training on sport performance. The neurostimulation techniques can be safe if they are applied at low intensities (< 4 mA) for a duration not longer than one hour/ day, although their impact depends upon a number of parameters (e.g., dimension and placement of the electrodes, frequency of their application). Given that little evidence is available about neurostimulation techniques applied to sports, it is difficult to suggest specific guidelines for their "correct" use, but we highlight that such techniques should not be administered without expert advice.